A zinc negative electrode material for alkaline secondary battery and its preparation method and application

By using ZnO/ZnS/C composite or metal-doped ZnO/ZnS/C composite as zinc negative electrode materials, the problem of zinc negative electrodes being easily formed and dissolved in alkaline secondary batteries is solved, and the cycle stability and capacity performance of the battery are significantly improved.

CN115548282BActive Publication Date: 2025-03-04HENAN NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211042482.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-29
Publication Date
2025-03-04
Estimated Expiration
2042-08-29

AI Technical Summary

Technical Problem

The zinc negative electrode of an alkali secondary battery is prone to form dendrite during charging and discharging, causing the battery to be short-circuited and easily dissolved and deformed in the alkaline electrolyte, reducing the cycle life of the battery.

Method used

ZnO/ZnS/C composite material or metal-doped ZnO/ZnS/C composite material is used as zinc negative electrode material. The electrical properties and structural stability of the material are improved through high-temperature calcination treatment and functional metal element doping.

Benefits of technology

Effectively inhibit the growth of zinc dendrites, reduce the solubility of zinc electrodes, improve the circulation stability and capacity performance of zinc negative electrodes, and extend the cycle service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115548282B_ABST
    Figure CN115548282B_ABST
Patent Text Reader

Abstract

The present invention discloses an alkaline secondary battery zinc negative electrode material and a preparation method and application thereof, belonging to the technical field of alkaline secondary batteries. The technical scheme of the present invention is as follows: the alkaline secondary battery zinc negative electrode material is mainly composed of a ZnO / ZnS / C composite material or a metal-doped ZnO / ZnS / C composite material. The present invention also specifically discloses a preparation method of the zinc negative electrode material for an alkaline secondary battery and an alkaline secondary battery using the negative electrode material. The novel alkaline secondary battery negative electrode material of the present invention can reduce the deformation of the zinc electrode, inhibit the growth, hydrogen evolution, and passivation of zinc dendrites, improve the stability of the zinc negative electrode in alkaline solution, and greatly improve the cycle life of the alkaline secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alkaline secondary battery negative electrode materials, and in particular relates to an alkaline secondary battery zinc negative electrode material and a preparation method and application thereof. Background Art

[0002] With the increasing depletion of non-renewable energy and the worsening of environmental problems, the demand for electrochemical energy storage systems used in modern electric vehicles and large-scale power grids is growing rapidly. Recently, low-cost, high-safety and environmentally friendly rechargeable batteries have attracted the attention of more and more researchers. In particular, alkaline secondary batteries are widely used in various energy storage devices due to their unique advantages such as high energy efficiency, easy miniaturization and green environmental protection. However, the zinc negative electrode used in this type of battery will undergo side reactions during the charging and discharging process to form dendrites. The needle-like structure of the dendrites makes it easy to pierce the diaphragm, causing the battery to short-circuit and reduce the cycle life of the battery; and the zinc negative electrode is easy to dissolve and deform in the alkaline electrolyte, resulting in a reduction in the effective area of ​​the electrode and a reduction in the utilization rate of the active material, which in turn affects the cycle life of the battery.

[0003] In order to solve the inherent defects of zinc negative electrode in alkaline electrolyte and reduce the solubility of zinc negative electrode in alkaline electrolyte, people have proposed methods such as protective layer coating and the use of additives to modify zinc negative electrode materials. Among them, the modification of materials using additives includes negative electrode additives, electrolyte additives, etc. Negative electrode additives include metal oxides or hydroxides such as Al2O3, In2O3 and Bi2O3, etc. Each additive has a positive effect on inhibiting hydrogen precipitation, zinc negative electrode deformation or self-discharge. Electrolyte additives usually include fluorides, arsenates, chromates, etc., which can inhibit passivation and improve capacity retention. In addition, researchers have also discovered some new negative electrode materials such as calcium zincate, zinc aluminum hydrotalcite and other materials for alkaline secondary battery zinc negative electrode. Although these new materials have improved the cycle performance of alkaline secondary batteries to a certain extent, they limit the rate performance of secondary batteries. The development of new zinc negative electrode materials is still an important means to solve the zinc negative electrode problem and promote the rapid development of zinc-nickel batteries. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a zinc negative electrode material for an alkaline secondary battery and a preparation method thereof. The zinc negative electrode material can effectively reduce the deformation of the zinc electrode, inhibit the growth of zinc dendrites and improve the stability of the zinc negative electrode in alkaline solution, thereby greatly improving the cycle life of the alkaline secondary battery.

[0005] The present invention adopts the following technical scheme to solve the above technical problems. A zinc negative electrode material for an alkaline secondary battery is characterized in that: the zinc negative electrode material is a ZnO / ZnS / C composite material or a metal-doped ZnO / ZnS / C composite material, the mass percentage of carbon element in the ZnO / ZnS / C composite material is 2% to 20%, the molar ratio of sulfur element to zinc element is 0.2 to 1:1, the particle size of the ZnO / ZnS / C composite material is 50 to 500 nm, and the functional metal element doped in the metal-doped ZnO / ZnS / C composite material is one or more of Al, Ti, Bi, Pb, In, Sn, Sb, Yb, Y, Er, La, Zr or Cr, and the doping mass percentage of the functional metal element is ≤25%;

[0006] Zinc sulfate and high molecular organic matter are used as main raw materials, mixed evenly and then calcined at high temperature in an inert gas atmosphere to obtain a ZnO / ZnS / C composite material;

[0007] Alternatively, zinc sulfate and high molecular organic matter are used as main raw materials, and then mixed evenly with functional metal salts, and calcined at high temperature in an inert gas atmosphere to obtain a metal-doped ZnO / ZnS / C composite material;

[0008] The functional metal salt is one or more of aluminum sulfate, titanium sulfate, bismuth sulfate, lead sulfate, indium sulfate, tin sulfate, antimony sulfate, ytterbium sulfate, yttrium sulfate, erbium sulfate, lanthanum sulfate, zirconium sulfate or chromium sulfate, and the high molecular organic matter is one or more of polyacrylamide, polyvinyl alcohol, citric acid, acrylate, ascorbic acid or glucose.

[0009] A method for preparing a zinc negative electrode material for an alkaline secondary battery, characterized in that the specific steps are:

[0010] Step S1, dispersing zinc sulfate or zinc sulfate and functional metal salt in deionized water, adding high molecular weight organic matter, stirring and mixing evenly, and freeze-drying at -20 to -40°C for 5 to 48 hours to obtain a precursor;

[0011] Step S2, placing the precursor obtained in step S1 in a tube furnace, heating it to 120-250° C. and keeping it constant for 10-120 min under an inert gas atmosphere, then continuing to heat it to 500-850° C. and keeping it constant for 1-24 h, then cooling it to room temperature, crushing it, and sieving it to obtain a zinc negative electrode material or a metal-doped zinc negative electrode material.

[0012] It is further defined that when no functional metal salt is added, the mass ratio of the zinc sulfate, the high molecular organic matter and the deionized water is 10:1 to 10:4 to 1000; when the functional metal salt is added, the mass ratio of the zinc sulfate, the high molecular organic matter, the functional metal salt and the deionized water is 10:1 to 10:0.1 to 14 to 1000.

[0013] A zinc negative electrode plate for an alkaline secondary battery, characterized in that the zinc negative electrode plate is made from the above alkaline secondary battery zinc negative electrode material.

[0014] A method for preparing a zinc negative electrode plate for an alkaline secondary battery, characterized in that the specific steps are:

[0015] Step S1, 50 wt% to 85 wt% of an alkaline secondary battery zinc negative electrode material, 2 wt% to 35 wt% of an additive and 3 wt% to 20 wt% of a conductive agent are mixed evenly, and then added to a binder aqueous solution prepared with 1 wt% to 5 wt% of a binder, and stirred and mixed evenly to obtain an active material slurry;

[0016] Step S2, coating the prepared active material slurry on a conductive substrate, drying, tableting, and punching to obtain an alkaline secondary battery zinc negative electrode plate.

[0017] It is further defined that the additive in step S1 is one or more of antimony oxide, antimony-doped tin oxide, antimony stannate, bismuth stannate, zinc-tin hydrotalcite or copper-aluminum hydrotalcite, the conductive agent is one or two of graphene, carbon nanotubes, acetylene black, flake graphite, nitrogen carbide, titanium carbide, niobium carbide or titanium nitride, and the binder is one or more of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, acrylate or hydroxypropyl methylcellulose; and the conductive substrate in step S2 is copper mesh, tinned copper mesh, zinc mesh, zinc foil, copper-zinc alloy mesh, foam copper or foam zinc.

[0018] It is further defined that the molecular formulas of the zinc-tin hydrotalcite and the copper-aluminum hydrotalcite are respectively [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O] and [Cu x Al y (OH)2]·[(B a- ) b ·mH2O], where B a- OH - , Cl - 、F - , S 2- , PO4 3- 、SO4 2- 、CO32- 、NO3 - , BO2 - 、MoO4 2- WO4 2- , citrate, borate, benzoate, dodecylbenzenesulfonate, dodecyl sulfate or dodecylsulfonate, one or more, 0.9≥x≥0.5, y≥0.1, x+y=1, b>0, m>0.

[0019] An alkaline secondary battery comprises a battery housing, a plate group sealed in the battery housing and an electrolyte, wherein the plate group comprises a positive plate, a negative plate and a diaphragm, and is characterized in that the negative plate adopts the above-mentioned alkaline secondary battery negative plate.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] The present invention prepares a ZnO / ZnS / C composite material or a metal-doped ZnO / ZnS / C composite material for use as a zinc negative electrode material for an alkaline secondary battery. Since zinc oxide and zinc sulfide have a wide bandgap and a large exciton binding energy at room temperature, the combination of the two can improve electrical performance; and the carbon in the composite material can play a conductive role, and the carbon layer as a protective layer can reduce the contact between the negative electrode active material and the strong alkaline electrolyte. The carbon network support structure is beneficial to improving the rate performance of the material. When the ZnO / ZnS / C composite material or the metal-doped ZnO / ZnS / C composite material is used in an alkaline secondary battery, zinc sulfide interacts with carbon, greatly improving the problem of zinc negative electrode dissolution in a strong alkaline electrolyte, inhibiting the formation of zinc dendrites, and improving the cycle stability of the zinc electrode. In addition, more importantly, the doping of beneficial elements improves the hydrogen evolution overpotential of the electrode, which is beneficial to reducing the occurrence of hydrogen evolution reaction, has a significant corrosion inhibition effect, and greatly improves the structural stability and capacity performance of the zinc electrode. The 0.2C gram capacity of the new ZnO / ZnS / C composite material can reach about 560mAh / g, and the 5C capacity can reach about 500mAh / g. The alkaline secondary battery prepared using the new negative electrode material has the advantages of high specific energy, high specific power and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the XRD pattern of the ZnO / ZnS / C composite material prepared in Example 1;

[0023] Figure 2 is a SEM image of the ZnO / ZnS / C composite material prepared in Example 1;

[0024] Figure 3 This is the element distribution diagram of the ZnO / ZnS / C composite material prepared in Example 1. DETAILED DESCRIPTION

[0025] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0026] Example 1

[0027] Preparation of ZnO / ZnS / C composite materials:

[0028] 10 g of zinc sulfate was dissolved in 30 mL of deionized water, and 1 g of citric acid was added, the mixture was stirred and mixed evenly, and then freeze-dried at -30°C for 6 h to obtain a precursor; the precursor was placed in a tube furnace and heated to 200°C under an inert atmosphere for 90 min; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 800°C for 2 h, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material.

[0029] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=2 / 1,B a- =Cl - , b = 0.1, m = 2) preparation:

[0030] 1.82 g of zinc chloride, 1.74 g of tin tetrachloride and 6 g of urea were dissolved in 200 mL of deionized water, and magnetically stirred at room temperature for 1 hour to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and hydrothermally reacted at 120° C. for 48 hours; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 80° C. for 5 hours to obtain a white powder, which was zinc-tin hydrotalcite.

[0031] Application of ZnO / ZnS / C composite materials:

[0032] 7g of the synthesized ZnO / ZnS / C composite material, 1.5g of zinc-tin hydrotalcite, 1g of acetylene black, 0.3g of a polyvinyl alcohol solution with a mass concentration of 4%, and 0.2g of a polytetrafluoroethylene aqueous solution with a mass concentration of 50% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a copper mesh, and after drying, tableting, punching and other tableting processes, a negative electrode plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive electrode plate and a negative electrode plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0033] Example 2

[0034] Preparation of ZnO / ZnS / C composite materials:

[0035] 10 g of zinc sulfate was dissolved in 31 mL of deionized water, and 1 g of polyvinyl alcohol was added, the mixture was stirred and mixed evenly, and then freeze-dried at -31°C for 6 hours to obtain a precursor; the precursor was placed in a tube furnace and heated to 210°C under an inert atmosphere and kept constant for 85 minutes; the obtained mixture was kept constant at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 790°C and kept constant for 2 hours, and then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material.

[0036] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=3 / 1,B a- =Cl - , b = 0.1, m = 2) preparation:

[0037] 2.04 g of zinc chloride, 0.65 g of tin tetrachloride and 6 g of urea were dissolved in 200 mL of deionized water, and magnetically stirred at room temperature for 1.5 h to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 130° C. for 36 h; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 85° C. for 4 h to obtain a white powder, which was zinc-tin hydrotalcite.

[0038] Application of ZnO / ZnS / C composite materials:

[0039] 7g of the synthesized ZnO / ZnS / C composite material, 1g of zinc-tin hydrotalcite, 0.5g of antimony oxide, 1g of acetylene black, 0.3g of a polyvinyl alcohol solution with a mass concentration of 4%, and 0.2g of a polytetrafluoroethylene aqueous solution with a mass concentration of 50% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on the foamed zinc, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery is prepared. The conventional sintered positive plate and the negative plate are sandwiched between an alkaline battery separator, and are placed in a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH electrolyte with a mass concentration of 3% are injected to assemble into a semi-sealed alkaline secondary battery.

[0040] Example 3

[0041] Preparation of titanium-doped ZnO / ZnS / C composites:

[0042] 10 g of zinc sulfate and 0.1 g of titanium sulfate were dissolved in 51 mL of deionized water, and then 0.5 g of polyvinyl alcohol and 0.5 g of polyacrylamide were added, stirred and mixed evenly, and then freeze-dried at -34°C for 5 h to obtain a precursor; the precursor was placed in a tube furnace and heated to 210°C under an inert atmosphere for 80 min; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 810°C and kept at a constant temperature for 1.5 h, then cooled to room temperature, crushed, and sieved to obtain a titanium-doped ZnO / ZnS / C composite material.

[0043] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=4 / 1,B a- =Cl - , b = 0.1, m = 2) preparation:

[0044] 2.18 g of zinc chloride, 1.04 g of tin tetrachloride and 6 g of urea were dissolved in 200 mL of deionized water, and magnetically stirred at room temperature for 1 hour to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and hydrothermally reacted at 110° C. for 48 hours; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 80° C. for 6 hours to obtain a white powder, which was zinc-tin hydrotalcite.

[0045] Application of titanium-doped ZnO / ZnS / C composites:

[0046] 7.5g of the synthesized titanium-doped ZnO / ZnS / C composite material, 1g of zinc-tin hydrotalcite, 0.6g of flake graphite, 0.4g of carbonized nitrogen, 0.25g of a 4% polyvinyl alcohol solution and 0.25g of a 50% polytetrafluoroethylene aqueous solution were mixed evenly to prepare an active material slurry; the prepared active material slurry was coated on a tin-plated copper mesh, and after drying, sheeting, punching and other sheeting processes, a negative electrode plate for an alkaline secondary battery was prepared. The conventional sintered positive electrode plate and the negative electrode plate were sandwiched between an alkaline battery separator, and were placed in a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH with a mass concentration of 3% were injected to assemble a semi-sealed alkaline secondary battery.

[0047] Example 4

[0048] Preparation of titanium-doped ZnO / ZnS / C composites:

[0049] 10 g of zinc sulfate and 0.12 g of titanium sulfate were dissolved in 50 mL of deionized water, and then 0.4 g of polyvinyl alcohol and 0.6 g of polyacrylamide were added, stirred and mixed evenly, and then freeze-dried at -35°C for 4 hours to obtain a precursor; the precursor was placed in a tube furnace and heated to 220°C under an inert atmosphere for 80 minutes; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 800°C for 2 hours, then cooled to room temperature, crushed, and sieved to obtain a titanium-doped ZnO / ZnS / C composite material.

[0050] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=5 / 1,B a- =Cl - , b = 0.2, m = 1) preparation:

[0051] 2.33 g of zinc chloride, 0.89 g of tin tetrachloride and 6 g of urea were dissolved in 205 mL of deionized water, and magnetically stirred at room temperature for 1.5 h to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 120° C. for 40 h; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 80° C. for 5 h to obtain a white powder, which was zinc-tin hydrotalcite.

[0052] Application of titanium-doped ZnO / ZnS / C composites:

[0053] 7.5g of the synthesized titanium-doped ZnO / ZnS / C composite material, 0.7g of zinc-tin hydrotalcite, 0.3g of bismuth stannate, 0.6g of flake graphite, 0.4g of carbonized nitrogen, 0.4g of a 4% polyvinyl alcohol solution and 0.1g of a 50% polytetrafluoroethylene aqueous solution were mixed evenly to prepare an active material slurry; the prepared active material slurry was coated on a foam copper, and after drying, tableting, punching and other tableting processes, a zinc negative electrode for an alkaline secondary battery negative electrode was prepared. A conventional sintered positive plate and a negative plate were sandwiched between an alkaline battery separator, and loaded into a special simulated battery shell, and an electrolyte solution with a mass concentration of 35% KOH and a mass concentration of 3% LiOH was injected to assemble a semi-sealed alkaline secondary battery.

[0054] Example 5

[0055] Preparation of ZnO / ZnS / C composite materials doped with titanium, lead and indium:

[0056] 10g zinc sulfate, 0.1g titanium sulfate, 0.05g lead sulfate and 0.05g indium sulfate were dissolved in 70mL deionized water, 0.7g polyvinyl alcohol, 0.7g citric acid and 0.6g acrylate were added, stirred and mixed evenly, and then freeze-dried at -32°C for 6h to obtain a precursor; the precursor was placed in a tube furnace and heated to 180°C for 120min under an inert atmosphere; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 750°C for 2.5h, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with titanium, lead and indium.

[0057] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=2 / 1,B a- =NO3 - , b = 0.1, m = 2) preparation:

[0058] 2.97 g of zinc nitrate, 1.83 g of tin nitrate and 4.5 g of urea were dissolved in 150 mL of deionized water, and magnetically stirred at room temperature for 1.5 h to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 120° C. for 40 h; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 80° C. for 5 h to obtain a white powder, which was zinc-tin hydrotalcite.

[0059] Application of ZnO / ZnS / C composite materials doped with titanium, lead and indium:

[0060] 6g of the synthesized ZnO / ZnS / C composite material doped with titanium, lead and indium, 2g of zinc-tin hydrotalcite, 1g of acetylene black, 0.5g of titanium nitride, 0.1g of a polytetrafluoroethylene aqueous solution with a mass concentration of 50% and 0.4g of a polyvinyl alcohol solution with a mass concentration of 4% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a zinc mesh, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive plate and a negative plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0061] Example 6

[0062] Preparation of ZnO / ZnS / C composite materials doped with titanium, lead and indium:

[0063] 10g zinc sulfate, 0.08g titanium sulfate, 0.06g lead sulfate and 0.06g indium sulfate were dissolved in 72mL deionized water, 0.5g polyvinyl alcohol, 0.4g citric acid and 1.1g acrylate were added, stirred and mixed evenly, and then freeze-dried at -33°C for 6h to obtain a precursor; the precursor was placed in a tube furnace and heated to 19°C and kept constant for 110min under an inert atmosphere; the obtained mixture was kept constant at a temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 780°C and kept constant for 2h, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with titanium, lead and indium.

[0064] Zinc-tin hydrotalcite [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O](Zn / Sn=4 / 1,B a- =NO3 - , b = 0.1, m = 2) preparation:

[0065] 4.78 g of zinc nitrate, 1.47 g of tin nitrate and 6.05 g of urea were dissolved in 201 mL of deionized water, and magnetically stirred at room temperature for 1 hour to prepare a mixed solution; the obtained mixed solution was transferred into a reactor and hydrothermally reacted at 130° C. for 24 hours; after the precursor was cooled to room temperature, it was filtered, washed, and dried at 80° C. for 5 hours to obtain a white powder, which was zinc-tin hydrotalcite.

[0066] Application of ZnO / ZnS / C composite materials doped with titanium, lead and indium:

[0067] 6g of the synthesized ZnO / ZnS / C composite material doped with titanium, lead and indium, 1.5g of zinc-tin hydrotalcite, 0.5g of antimony stannate, 0.8g of acetylene black, 0.7g of titanium nitride, 0.3g of a polytetrafluoroethylene aqueous solution with a mass concentration of 50% and 0.2g of a polyvinyl alcohol solution with a mass concentration of 4% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a copper-zinc alloy mesh, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery is prepared. A conventional sintered positive plate and a negative plate are sandwiched between an alkaline battery separator, and are placed in a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH electrolyte with a mass concentration of 3% are injected to assemble a semi-sealed alkaline secondary battery.

[0068] Example 7

[0069] Preparation of ZnO / ZnS / C composite materials doped with aluminum and bismuth:

[0070] 10g zinc sulfate, 0.1g aluminum sulfate and 0.2g bismuth sulfate were dissolved in 90mL deionized water, 1.5g polyacrylamide and 1.5g citric acid were added, stirred and mixed evenly, and then freeze-dried at -33°C for 5.5h to obtain a precursor; the precursor was placed in a tube furnace and heated to 210°C for 80min under an inert atmosphere; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 780°C for 2h, then cooled to room temperature, crushed, and sieved to obtain an aluminum- and bismuth-doped ZnO / ZnS / C composite material.

[0071] Application of aluminum and bismuth doped ZnO / ZnS / C composite materials:

[0072] 7g of the synthesized aluminum-doped and bismuth-doped ZnO / ZnS / C composite material, 1.5g of zinc-tin hydrotalcite, 0.7g of acetylene black, 0.3g of titanium carbide, 0.3g of a 10% hydroxypropyl methylcellulose solution dissolved in polyvinyl alcohol, and 0.2g of a 50% polytetrafluoroethylene aqueous solution were mixed evenly to prepare an active material slurry; the prepared active material slurry was coated on a zinc foil, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery was prepared. An alkaline battery separator was sandwiched between a conventional sintered positive plate and a negative plate, and the plate was placed in a special simulated battery shell, and an electrolyte solution of 35% KOH and 3% LiOH was injected to assemble a semi-sealed alkaline secondary battery.

[0073] Example 8

[0074] Preparation of ZnO / ZnS / C composite materials doped with antimony and erbium:

[0075] 10g zinc sulfate, 0.2g antimony sulfate and 0.2g erbium sulfate were dissolved in 110mL deionized water, 0.4g acrylate was added, the mixture was stirred and mixed evenly, and then freeze-dried at -30°C for 6h to obtain a precursor; the precursor was placed in a tube furnace and heated to 200°C under an inert atmosphere and kept constant for 100min; the obtained mixture was kept constant at a temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 750°C and kept constant for 1.5 hours, then cooled to room temperature, crushed, and sieved to obtain an antimony- and erbium-doped ZnO / ZnS / C composite material.

[0076] Copper aluminum hydrotalcite [Cu x Al y (OH)2]·[(B a- ) b ·mH2O](Cu / Al=2 / 1,B a- =NO3 - , b = 0.1, m = 2) preparation:

[0077] Dissolve 3g of copper nitrate and 2.3g of aluminum nitrate in 50mL of deionized water, respectively, and record them as solution A and solution B; then weigh 1.3g of sodium carbonate and dissolve it in 50mL of deionized water to prepare a sodium carbonate aqueous solution with a concentration of 0.2mol / L, which is recorded as solution C; add solutions A and B to solution C at the same time under stirring at 50°C, and stop stirring when the pH reaches 9; place the mixed solution in an oven at 80°C for aging for 24h; after cooling to room temperature, wash the mixed solution with ethanol and water three times respectively, and dry it at 60°C for 8h to obtain copper-aluminum hydrotalcite powder.

[0078] Application of antimony and erbium doped ZnO / ZnS / C composite materials:

[0079] 8g of the synthesized ZnO / ZnS / C composite material doped with antimony and erbium, 0.3g of copper-aluminum hydrotalcite, 0.2g of antimony stannate, 0.7g of flake graphite, 0.3g of titanium nitride, 0.1g of a polyvinyl alcohol solution with a mass concentration of 4%, and 0.4g of a sodium carboxymethyl cellulose solution with a mass concentration of 8% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a copper-zinc alloy mesh, and a zinc negative electrode for an alkaline secondary battery negative electrode is prepared through drying, tableting, punching and other tableting processes. The sintered positive plate and the negative plate are sandwiched between an alkaline battery separator, and are placed in a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH electrolyte with a mass concentration of 3% are injected to assemble into a semi-sealed alkaline secondary battery.

[0080] Example 9

[0081] Preparation of Ytterbium- and Chromium-doped ZnO / ZnS / C Composite Materials:

[0082] 10g zinc sulfate, 0.2g ytterbium sulfate and 0.3g chromium sulfate were dissolved in 130mL deionized water, and then 2.5g polyacrylamide and 2.5g acrylate were added, stirred and mixed evenly, and then freeze-dried at -35°C for 5h to obtain a precursor; the precursor was placed in a tube furnace and heated to 210°C under an inert atmosphere for 90min; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 780°C for 2h, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with ytterbium and chromium.

[0083] Application of Ytterbium and Chromium Doped ZnO / ZnS / C Composite Materials:

[0084] 7g of the synthesized ZnO / ZnS / C composite material doped with ytterbium and chromium, 0.5g of antimony oxide, 0.5g of bismuth stannate, 0.6g of flake graphite, 0.9g of acetylene black, 0.4g of 10% hydroxypropyl methylcellulose solution and 0.1g of 50% polytetrafluoroethylene aqueous solution were mixed evenly to prepare active material slurry; the prepared active material slurry was coated on the foam copper, and the negative plate for alkaline secondary battery was prepared through drying, sheeting, punching and other sheeting processes. The conventional sintered positive plate and the negative plate were sandwiched between the alkaline battery separator, and loaded into a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH electrolyte with a mass concentration of 3% were injected to assemble into a semi-sealed alkaline secondary battery.

[0085] Example 10

[0086] Preparation of ZnO / ZnS / C composite materials doped with titanium, lanthanum and chromium:

[0087] 10g zinc sulfate, 0.2g titanium sulfate, 0.2g lanthanum sulfate and 0.2g chromium sulfate are dissolved in 150mL deionized water, and then 3g polyacrylamide and 3g acrylate are added, stirred and mixed evenly, and then freeze-dried at -30°C for 6h to obtain a precursor; the precursor is placed in a tube furnace and heated to 200°C under an inert atmosphere and kept at a constant temperature for 100min; the obtained mixture is kept at a constant temperature and then placed in a tube furnace under an inert atmosphere and heated to 800°C and kept at a constant temperature for 1.5h, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with titanium, lanthanum and chromium.

[0088] Application of ZnO / ZnS / C composite materials doped with titanium, lanthanum and chromium:

[0089] 6.5g of the synthesized ZnO / ZnS / C composite material doped with titanium, lanthanum and chromium, 1.5g of antimony stannate, 0.5g of bismuth stannate, 0.7g of flake graphite, 0.3g of niobium carbide, 0.3g of sodium carboxymethyl cellulose solution with a mass concentration of 8% and 0.2g of hydroxypropyl cellulose solution with a mass concentration of 10% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on zinc foam, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive plate and a negative plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0090] Embodiment 11

[0091] Preparation of ZnO / ZnS / C composite materials doped with Sn, Yttrium and Er:

[0092] 10g zinc sulfate, 0.1g tin sulfate, 0.2g yttrium sulfate and 0.3g erbium sulfate were dissolved in 170mL deionized water, and 3.5g polyacrylamide and 3.5g ascorbic acid were added, stirred and mixed evenly, and then freeze-dried at -31°C for 350min to obtain a precursor; the precursor was placed in a tube furnace and heated to 190°C for 130min under an inert atmosphere; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 700°C for 160min, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with tin, yttrium and erbium.

[0093] Copper aluminum hydrotalcite [Cu x Al y (OH)2]·[(B a- ) b ·mH2O](Cu / Al=3 / 1,B a- =Cl-, b = 0.1, m = 2) preparation:

[0094] 1.02g of copper chloride and 0.34g of aluminum chloride were dissolved in 51mL of deionized water, respectively, and recorded as solution A and solution B; then 1.28g of sodium carbonate was weighed and dissolved in 50mL of deionized water to prepare a sodium carbonate aqueous solution with a concentration of 0.2mol / L, recorded as solution C; solutions A and B were simultaneously added dropwise to solution C under stirring at 50°C, and stirring was stopped when the pH reached 10; the mixed solution was placed in a 70°C oven for aging for 30h; after cooling to room temperature, the mixed solution was washed 3 times with ethanol and water respectively, and dried at 80°C for 5h to obtain copper-aluminum hydrotalcite powder.

[0095] Application of ZnO / ZnS / C composite materials doped with Sn, Yttrium and Erbium:

[0096] 7.5g of the synthesized ZnO / ZnS / C composite material doped with tin, yttrium and erbium, 0.5g of copper-aluminum hydrotalcite, 0.5g of bismuth stannate, 0.5g of graphene, 0.5g of carbon nanotubes and 0.5g of styrene-butadiene rubber aqueous solution with a mass concentration of 50% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a copper mesh, and after drying, tableting, punching and other tableting processes, a negative electrode plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive electrode plate and a negative electrode plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0097] Example 12

[0098] Preparation of ZnO / ZnS / C composite materials doped with lanthanum, zirconium and antimony:

[0099] 10g zinc sulfate, 0.3g lanthanum sulfate, 0.3g zirconium sulfate and 0.2g antimony sulfate were dissolved in 190mL deionized water, 8g ascorbic acid was added, stirred and mixed evenly, and then freeze-dried at -32°C for 340min to obtain a precursor; the precursor was placed in a tube furnace and heated to 220°C and kept constant for 85min under an inert atmosphere; the obtained mixture was kept constant at a temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 730°C and kept constant for 140min, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with lanthanum, zirconium and antimony.

[0100] Application of ZnO / ZnS / C composite materials doped with lanthanum, zirconium and antimony:

[0101] 7.5g of the synthesized ZnO / ZnS / C composite material doped with lanthanum, zirconium and antimony, 1g of tin-doped antimony oxide, 0.5g of graphene, 0.5g of carbon nanotubes and 0.5g of hydroxypropyl cellulose solution with a mass concentration of 10% are mixed evenly to prepare an active material slurry; the prepared active material slurry is coated on a tin-plated copper mesh, and the negative electrode plate for alkaline secondary batteries is prepared through drying, tableting, punching and other tableting processes. The conventional sintered positive plate and the negative plate are sandwiched between an alkaline battery separator, and are placed in a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH with a mass concentration of 3% are injected to assemble into a semi-sealed alkaline secondary battery.

[0102] Example 13

[0103] Preparation of ZnO / ZnS / C composite materials doped with aluminum, titanium, indium and chromium:

[0104] 10g zinc sulfate, 0.2g aluminum sulfate, 0.2g titanium sulfate, 0.2g indium sulfate and 0.1g chromium sulfate are dissolved in 210mL deionized water, 4.5g glucose and 4.5g polyvinyl alcohol are added, stirred and mixed evenly, and then freeze-dried at -34°C for 330min to obtain a precursor; the precursor is placed in a tube furnace and heated to 180°C for 115min under an inert atmosphere; the obtained mixture is kept at a constant temperature and then placed in a tube furnace under an inert atmosphere and heated to 760°C for 130min, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with aluminum, titanium, indium and chromium.

[0105] Application of ZnO / ZnS / C composite materials doped with aluminum, titanium, indium and chromium:

[0106] 8g of the synthesized ZnO / ZnS / C composite material doped with aluminum, titanium, indium and chromium, 0.2g of bismuth stannate, 0.3g of antimony oxide, 0.5g of graphene, 0.5g of flake graphite, 0.1g of styrene-butadiene rubber aqueous solution with a mass concentration of 50% and 0.4g of polyvinyl alcohol aqueous solution with a mass concentration of 4% are mixed evenly to prepare active material slurry; the prepared active material slurry is coated on a zinc mesh, and after drying, sheeting, punching and other sheeting processes, a negative plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive plate and a negative plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0107] Embodiment 14

[0108] Preparation of ZnO / ZnS / C composite materials doped with bismuth, antimony, lanthanum and indium:

[0109] 10g zinc sulfate, 0.25g bismuth sulfate, 0.25g antimony sulfate, 0.25g lanthanum sulfate and 0.25g indium sulfate were dissolved in 230mL deionized water, 4g glucose, 3g polyvinyl alcohol and 3g citric acid were added, stirred and mixed evenly, and then freeze-dried at -35°C for 5h to obtain a precursor; the precursor was placed in a tube furnace and heated to 230°C for 75min under an inert atmosphere; the obtained mixture was kept at a constant temperature and then continued to be placed in a tube furnace under an inert atmosphere and heated to 790°C for 135min, then cooled to room temperature, crushed, and sieved to obtain a ZnO / ZnS / C composite material doped with bismuth, antimony, lanthanum and indium.

[0110] Application of ZnO / ZnS / C composite materials doped with bismuth, antimony, lanthanum and indium:

[0111] 7.5g of the synthesized ZnO / ZnS / C composite material doped with bismuth, antimony, lanthanum and indium, 0.7g of antimony oxide, 0.3g of antimony stannate, 0.5g of graphene, 0.5g of carbonized nitrogen, 0.23g of 50% styrene-butadiene rubber aqueous solution and 0.23g of 4% polyvinyl alcohol aqueous solution were mixed evenly to prepare active material slurry; the prepared active material slurry was coated on zinc foil, and after drying, sheeting, punching and other sheeting processes, the negative plate for alkaline secondary battery was prepared. The conventional sintered positive plate and the negative plate were sandwiched between the alkaline battery separator, and loaded into a special simulated battery shell, and KOH with a mass concentration of 35% and LiOH electrolyte with a mass concentration of 3% were injected to assemble into a semi-sealed alkaline secondary battery.

[0112] Comparative Example 1

[0113] Commercial zinc oxide was used as the negative electrode material.

[0114] 7.5g of commercial zinc oxide, 0.5g of bismuth oxide, 0.5g of flake graphite, 0.5g of acetylene black, 0.6g of hydroxypropyl methylcellulose solution with a mass concentration of 5%, and 0.4g of polyvinyl alcohol solution with a mass concentration of 4% are mixed evenly to prepare active material slurry; the prepared active material slurry is coated on a conductive substrate, and after drying, tableting, punching and other tableting processes, a negative plate for an alkaline secondary battery is prepared. An alkaline battery separator is sandwiched between a conventional sintered positive plate and a negative plate, and the plate is placed in a special simulated battery shell, and an electrolyte with a mass concentration of 35% KOH and a mass concentration of 3% LiOH is injected to assemble a semi-sealed alkaline secondary battery.

[0115] The alkaline secondary batteries assembled in Examples 1-14 and Comparative Example 1 were tested in the following manner:

[0116] 1. Secondary battery capacity and rate performance test

[0117] After the secondary battery was activated at 0.2C, it was charged at 0.2C for 5 hours, and then the battery was left for 10 minutes. The rate performance was then measured at 0.2C, 1C, 5C and 10C to measure the capacity performance of the negative electrode material.

[0118] 2. Secondary battery cycle performance test

[0119] The secondary battery was subjected to 1C charge and discharge test at 25°C ambient temperature, and the test was terminated after 500 cycles. The capacity retention rate was calculated.

[0120] The above secondary battery performance test results are shown in Table 1.

[0121] Table 1 Battery performance test

[0122]

[0123]

[0124] The above constant current charge and discharge test results show that the nanostructured ZnO / ZnS / C composite material and the ZnO / ZnS / C composite material doped with beneficial elements such as indium, lead, bismuth, and ytterbium have greatly improved the cycle performance of the zinc negative electrode. At 0.2C, the average discharge capacity is 552.2mAh / g, and the capacity retention rate is 98.1% after 1C cycles 500 times. However, the commercial zinc oxide has a discharge capacity of 502mAh / g at 0.2C, and the capacity retention rate is only 40.8% after 1C cycles 500 times. It can be clearly seen that the alkaline secondary battery assembled with the alkaline secondary battery zinc negative electrode material prepared by the present invention has a higher gram capacity, better rate performance and excellent cycle stability performance, all of which are better than commercial zinc oxide and can meet the requirements of commercial batteries, especially high-capacity, high-power and long-life batteries. The improvement of these properties is mainly attributed to: optimization of the synthesis method, construction of the carbon network support structure, selection of new additives, interaction between zinc sulfide and carbon in the composite material, and the presence of a large number of beneficial metal elements, which greatly reduce the deformation of the zinc negative electrode and significantly inhibit its hydrogen evolution reaction, thereby improving the overall performance of the zinc negative electrode. The alkaline secondary battery prepared by the zinc negative electrode material synthesized by the present invention has the advantages of good rate performance and long cycle life.

[0125] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. An alkaline secondary battery zinc negative electrode material, characterized in that: The zinc negative electrode material is a metal-doped ZnO / ZnS / C composite material, the mass percentage of carbon element in the material is 2%~20%, the molar ratio of sulfur element to zinc element is 0.2~1:1, the particle size of the material is 50~500nm, and the doped functional metal element is one or more of Al, Ti, Bi, Pb, In, Sn, Sb, Yb, Y, Er, La, Zr or Cr, and the doping mass percentage is ≤25%; Zinc sulfate and high molecular organic matter are used as main raw materials, and then mixed evenly with functional metal salts, and calcined at high temperature in an inert gas atmosphere to obtain a metal-doped ZnO / ZnS / C composite material; the functional metal salt is one or more of aluminum sulfate, titanium sulfate, bismuth sulfate, lead sulfate, indium sulfate, tin sulfate, antimony sulfate, ytterbium sulfate, yttrium sulfate, erbium sulfate, lanthanum sulfate, zirconium sulfate or chromium sulfate, and the high molecular organic matter is one or more of polyacrylamide, polyvinyl alcohol, citric acid, acrylate, ascorbic acid or glucose; The specific preparation process of the zinc negative electrode material is as follows: Step S1, dispersing zinc sulfate and functional metal salt in deionized water, adding high molecular organic matter, stirring and mixing evenly, and freeze-drying at -20 to -40°C for 5 to 48 hours to obtain a precursor, wherein the mass ratio of zinc sulfate, high molecular organic matter, functional metal salt and deionized water is 10:1 to 10:0.1 to 14 to 1000; Step S2, placing the precursor obtained in step S1 in a tube furnace, heating it to 120-250° C. and keeping it constant for 10-120 min under an inert gas atmosphere, then continuing to heat it to 500-850° C. and keeping it constant for 1-24 h, then cooling it to room temperature, crushing it, and sieving it to obtain a metal-doped zinc negative electrode material; The zinc negative electrode material can reduce the deformation of the zinc electrode, inhibit the growth of zinc dendrites and improve the stability of the zinc negative electrode in alkaline solution, thereby increasing the cycle life of the alkaline secondary battery.

2. An alkaline secondary battery zinc negative plate, characterized in that The zinc negative electrode plate is made from the alkaline secondary battery zinc negative electrode material according to claim 1.

3. A method for preparing a zinc negative electrode plate for an alkaline secondary battery according to claim 2, characterized in that The specific steps are: Step S1, 50 wt% to 85 wt% of an alkaline secondary battery zinc negative electrode material, 2 wt% to 35 wt% of an additive and 3 wt% to 20 wt% of a conductive agent are mixed evenly, and then added to a binder aqueous solution prepared with 1 wt% to 5 wt% of a binder, and stirred and mixed evenly to obtain an active material slurry; Step S2, coating the prepared active material slurry on a conductive substrate, drying, tableting, and punching to obtain an alkaline secondary battery zinc negative electrode plate.

4. The method for preparing the zinc negative electrode plate of the alkaline secondary battery according to claim 3, characterized in that: The additive in step S1 is one or more of antimony oxide, antimony-doped tin oxide, antimony stannate, bismuth stannate, zinc-tin hydrotalcite or copper-aluminum hydrotalcite, the conductive agent is one or two of graphene, carbon nanotubes, acetylene black, flake graphite, nitrogen carbide, titanium carbide, niobium carbide or titanium nitride, and the binder is one or more of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, acrylate or hydroxypropyl methylcellulose; the conductive substrate in step S2 is copper mesh, tinned copper mesh, zinc mesh, zinc foil, copper-zinc alloy mesh, foamed copper or foamed zinc.

5. The method for preparing the zinc negative electrode plate of the alkaline secondary battery according to claim 4, characterized in that: The molecular formulas of the zinc-tin hydrotalcite and the copper-aluminum hydrotalcite are respectively [Zn x Sn y (OH)2]·[(B a- ) b ·mH2O] and [Cu x Al y (OH)2]·[(B a- ) b ·mH2O], where B a- OH − , Cl - 、F - , S 2- PO4 3- 、SO4 2- 、CO3 2− 、NO3 − , BO2 - 、MoO4 2- WO4 2- , citrate, borate, benzoate, dodecylbenzenesulfonate, dodecyl sulfate or dodecylsulfonate, one or more, 0.9≥x≥0.5, y≥0.1, x+y=1, b>0, m>0.

6. An alkaline secondary battery, comprising a battery housing, a plate group sealed in the battery housing, and an electrolyte, wherein the plate group comprises a positive plate, a negative plate, and a separator, characterized in that: The negative electrode plate is the alkaline secondary battery negative electrode plate as claimed in claim 2.

Citation Information

Patent Citations

  • Alkaline battery negative pole material and preparation method thereof

    CN102931385A

  • Negative electrode mixture or gel electrolyte, and battery using said negative electrode mixture or said gel electrolyte

    CN103748710A

  • Preparation method of lithium ion battery anode material

    CN108963214A